Transnational cooperation in enhancing researchers’ wider employability: the TRANSPEER project - Lees, J. (2022)
The purpose of this paper is to provide an example of best practice towards enhancing employability in the cross-sectoral labour market for doctorate-holders. This was achieved through an Erasmus+ KA2 (Strategic Partnership) skills development project which created a training programme (TRANSPEER) involving a multi-disciplinary cohort of researchers at a range of career stages, drawn from universities in Norway, Portugal, Sweden and the UK.